CHARACTER EDUCATION IMPLEMENTATIONTHROUGH ART LEARNING FOR LEARNING PARTICIPANTS OF SENIOR HIGH SCHOOL THROUGH DANCE CREATION - Etik Riyaningsih; Maryono Maryono; Harini Harini (Proceeding of International Conference on Art, Language, and Culture, 2017)
Character-based education needs to be developed in the world of education in Indonesia as an effort to achieve the goal of national education and building citizens who have competence not only in cognitive areaand but also affective and psychomotoric. Senior High School is one of the educational institution that implements the art and culture learningformally as a medium of character development of learners through the learning of dance. The study aimed to describe the implementation of character education in the learning activities of dance art by creating dance creations. The study used a qualitative approach. Sources of data are in the form of informants, documents, places and events. The data collection techniques used are observation, interview, documentation and recording. Data validity techniques usedare triangulation source and triangulationmethod. Technique of data analysis using interactive analysis model by reducing data, data presentation and verification. The result of research shows that dance art learning in implementation to form character with dance work process they are knowledge and skill. 1) Knowledge is shown through function, technique, form, type and aesthetic value according to accompaniment form religious values 2) Skill is shown through dance movement creations according to accompaniment presented in groups that can form the value of cooperation.